Competitiveness of chia against brassica weeds improves through a narrow spatial arrangement - Anuch Tiranti, Juan Valentín (2025)
Chia (Salvia hispanica L.) is a promising crop valued as a sustainable source of omega-3. However, chia yield and quality are reduced because of weed competition and the lack of registered herbicides. This study evaluated how chia spatial arrangement suppresses weed growth and provided management options for this crop. The performance of chia plants was assessed over three growing seasons in field experiments using a factorial design that considered spatial arrangement (narrow and wide), weed management (control without weeds, soil bank brassica (Brassica rapa L.), and sown brassica), and cover crop (with or without a rye (Secale cereale L.) cover crop during chia fallow). Chia and brassica are not complementary, leading to resource competition (relative yield total around 1) and negative effects on each other. A significant decrease in chia grain yield of 0.9% per unit increase in the percentage of weeds in total biomass was observed. As chia had a competitive advantage over brassica, the grain yield reduction was ameliorated with a narrow spatial arrangement. Narrow spatial arrangement promotes faster canopy closure during the early growth stages, decreasing light penetration and suppressing weed growth. The high extinction coefficient of chia (0.91) and the low critical LAI (3.3) contributed to this light interception behavior. Accordingly, to maximize chia productivity and profitability, a narrow spatial arrangement is an effective management strategy to suppress weeds. This study contributes valuable insights into chia-weed interactions and emphasizes the importance of sustainable crop management practices.